Electrode active material, electrode mixture, battery, and manufacturing method thereof
By integrating a specific crystallite size range of silicon clathrate II crystal phase with diamond-type silicon in the electrode active material, the volume change issues during charging and discharging are mitigated, improving battery stability and performance.
Patent Information
- Application Number
- JP2023168609
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-04-09
AI Technical Summary
Silicon-based electrode active materials experience significant volume changes during charging and discharging, leading to deterioration of electrode function over repeated cycles.
The electrode active material incorporates a combination of silicon clathrate II crystal phase and diamond-type silicon crystal phase, with a crystallite size of the silicon clathrate II phase ranging from 125 nm to 215 nm, to minimize volume changes during charge and discharge.
This approach results in an electrode active material with a small volume change due to charge and discharge, thereby enhancing the stability and performance of the battery over repeated cycles.
Smart Images

Figure 2025058589000001_ABST
Abstract
Description
[Technical Field]
[0001] The present disclosure relates to an electrode active material, an electrode mixture, a battery, and methods for producing the same. [Background technology]
[0002] In recent years, the development of batteries has been actively pursued. For example, in the automotive industry, development of batteries for use in electric vehicles (BEVs), plug-in hybrid electric vehicles (PHEVs), or hybrid electric vehicles (HEVs) is underway. In addition, silicon (Si) is known as an electrode active material used in batteries. For example, Patent Document 1 discloses an electrode active material having a silicon clathrate II type crystalline phase and having voids inside the primary particles. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent Publication No. 2021-158004 Summary of the Invention [Problem to be solved by the invention]
[0004] Silicon has a large theoretical capacity and is effective in increasing the energy density of batteries. However, its volume changes significantly during charging and discharging. This large volume change can lead to problems such as a deterioration in the functionality of the electrode active material after repeated charging and discharging.
[0005] The present disclosure has been made in view of the above circumstances, and has as its main object to provide an electrode active material that undergoes little volume change upon charge and discharge. [Means for solving the problem]
[0006] In order to solve the above problems, the present inventors have conducted extensive research and have found that when an electrode active material has a small amount of diamond-type silicon crystalline phase in addition to a silicon clathrate II crystalline phase, the volume change during charging and discharging is suppressed. At the same time, the present inventors have found that even if the proportion of diamond-type silicon crystalline phase in an electrode active material is the same, there is a difference in the volume change during charging and discharging. After carefully examining the cause of this difference, the present inventors have found that the crystallite size of the silicon clathrate II crystalline phase has a significant impact on the volume change during charging and discharging, and have completed the following invention.
[0007] [1] An electrode active material having a silicon clathrate II type crystalline phase, The electrode active material, wherein the crystallite size of the crystalline phase is 125 nm or more and 215 nm or less.
[0008] [2] The electrode active material according to [1], wherein the crystallite size of the crystalline phase is 130 nm or more and 180 nm or less.
[0009] [3] The electrode active material according to [1] or [2], wherein the proportion of the diamond-type silicon crystal phase contained in the electrode active material is 0% by weight or more and 3% by weight or less.
[0010] [4] The electrode active material according to any one of [1] to [3], wherein the proportion of the diamond-type silicon crystal phase contained in the electrode active material is 0.2 wt % or more and 3 wt % or less.
[0011] [5] The electrode active material according to any one of [1] to [4], which has the silicon clathrate type II crystal phase as a main phase.
[0012] [6] The electrode active material according to any one of [1] to [5], wherein the electrode active material has voids inside the primary particles.
[0013] [7] The electrode active material according to [6], wherein the proportion of the voids is 4% or more and 40% or less.
[0014] [8] An electrode mixture comprising the electrode active material according to any one of [1] to [7] and at least one of a conductive material and a binder.
[0015] [9] The electrode mixture according to [8], wherein the electrode mixture further contains a solid electrolyte.
[0016]
[10] The electrode mixture according to [9], wherein the solid electrolyte contained in the electrode mixture is a sulfide solid electrolyte.
[0017]
[11] A battery having a positive electrode layer, a negative electrode layer, and an electrolyte layer disposed between the positive electrode layer and the negative electrode layer, A battery in which the positive electrode layer or the negative electrode layer contains the electrode mixture according to any one of [8] to
[10] .
[0018]
[12] The battery according to
[11] , wherein the negative electrode layer contains the electrode mixture.
[0019]
[13] The battery according to
[11] or
[12] , wherein the electrolyte layer contains a solid electrolyte.
[0020]
[14] the solid electrolyte included in the electrolyte layer is a sulfide solid electrolyte, The battery according to
[13] , wherein the thickness of the electrolyte layer is 0.1 μm or more and 100 μm or less.
[0021]
[15] The battery according to any one of
[11] to
[14] , wherein the positive electrode layer contains a rock salt layered active material.
[0022]
[16] an alloying step of reacting a Na source and a Si source to obtain a Na-Si alloy; a firing step of firing the Na-Si alloy to reduce the amount of Na in the Na-Si alloy and generate a silicon clathrate type II crystalline phase; and The firing step is a first firing treatment in which the Na-Si alloy is fired at a temperature of less than 340°C; a second firing treatment in which the compound subjected to the first firing treatment is fired at a temperature of 340°C or higher; A method for producing an electrode active material, comprising:
[0023]
[17]
[16] The method for producing an electrode active material according to
[16] , wherein the firing conditions are adjusted in the firing step so that the crystallite size of the crystalline phase is 125 nm or more and 215 nm or less.
[0024]
[18] A preparation step of preparing an electrode active material by the method for producing an electrode active material according to
[16] or
[17] ; a mixing step of mixing the electrode active material with at least one of a conductive material and a binder to obtain an electrode mixture; The method for producing an electrode mixture comprising the steps of:
[0025]
[19] A preparation step of preparing an electrode active material by the method for producing an electrode active material according to
[16] or
[17] ; a mixing step of mixing the electrode active material with at least one of a conductive material and a binder to obtain an electrode mixture; an electrode layer forming step of forming an electrode layer using the electrode mixture; A method for manufacturing a battery comprising the steps of: [Effects of the Invention]
[0026] The present disclosure has an effect of being able to obtain an electrode active material that undergoes little volume change upon charge and discharge. [Brief explanation of the drawings]
[0027] [Figure 1] FIG. 2 is a schematic perspective view illustrating the crystalline phase of Si. [Figure 2] FIG. 1 is a schematic cross-sectional view illustrating a battery according to the present disclosure. [Figure 3] 1 is a flowchart illustrating a method for producing an electrode active material according to the present disclosure. [Figure 4] 1 shows the results of the volume expansion rate of batteries using the electrode active materials obtained in Examples 1 to 5 and Comparative Examples 1 and 2. DETAILED DESCRIPTION OF THE INVENTION
[0028] The electrode active material, electrode mixture, battery, and manufacturing methods thereof according to the present disclosure will be described in detail below.
[0029] A. Electrode active material The electrode active material according to the present disclosure has a silicon clathrate II crystalline phase, and the crystallite size of the silicon clathrate II crystalline phase is typically 125 nm or more and 215 nm or less.
[0030] According to the present disclosure, since the crystallite size of the silicon clathrate II crystalline phase is within a predetermined range, the electrode active material exhibits small volume change during charge and discharge. As described above, Si has a large theoretical capacity and is effective in increasing the energy density of batteries. On the other hand, Si exhibits large volume change during charge and discharge. If the volume change during charge and discharge is large, there is a problem that the function of the electrode active material is likely to deteriorate when the electrode active material is repeatedly charged and discharged. In response to this problem, the present inventors have conducted extensive research and have found that when the electrode active material has a small amount of diamond-type silicon crystalline phase in addition to the silicon clathrate II crystalline phase, the volume change during charge and discharge is suppressed.
[0031] At the same time, the inventors have discovered a new finding that even if the proportion of diamond-type silicon crystalline phase in the electrode active material is the same, there is a difference in the volume change during charge and discharge. That is, they have discovered a new finding that there is a phenomenon that cannot be explained solely by the proportion of diamond-type silicon crystalline phase. Therefore, the inventors have investigated in detail the cause of the above difference and discovered that the crystallite size of the silicon clathrate II crystalline phase has a significant impact on the volume change during charge and discharge.
[0032] Specifically, the inventors have found that volume change during charge and discharge can be suppressed by adjusting the crystallite size of the silicon clathrate II crystalline phase to a relatively small size. It is speculated that the reason volume change can be suppressed is that adjusting the crystallite size to a relatively small size accelerates Li diffusion within the particles of the electrode active material, thereby suppressing uneven reactions within the particles. On the other hand, it has also been found that volume change cannot be suppressed if the crystallite size of the silicon clathrate II crystalline phase is made too small. It is speculated that the reason volume change cannot be suppressed is that if the crystallite size is too small, distortion is likely to occur in the crystalline structure of the silicon clathrate II crystalline phase, making it impossible to maintain the crystalline structure.
[0033] The electrode active material according to the present disclosure has a silicon clathrate II crystalline phase. As shown in FIG. 1(a), in the silicon clathrate II crystalline phase, multiple Si elements form polyhedra (cages) containing pentagons or hexagons. These polyhedra have internal spaces capable of encapsulating metal ions such as Li ions. The insertion of metal ions into these spaces can suppress volumetric changes during charging and discharging. In particular, in all-solid-state batteries, high confining pressures are generally required to suppress volumetric changes during charging and discharging. However, the use of the electrode active material according to the present disclosure can reduce the confining pressure, thereby preventing the need for larger confining jigs. On the other hand, as shown in FIG. 1(b), in the diamond-type silicon crystalline phase, multiple Si elements form tetrahedra. Because the tetrahedra do not have internal spaces capable of encapsulating metal ions such as Li ions, the diamond-type silicon crystalline phase is less able to suppress volumetric changes during charging and discharging than the silicon clathrate II crystalline phase. However, if the electrode active material contains a small amount of diamond-type silicon crystal phase, the volume change due to charging and discharging can sometimes be suppressed.
[0034] The electrode active material according to the present disclosure has a silicon clathrate II crystalline phase. The crystallite size of the silicon clathrate II crystalline phase is typically 125 nm or more and 215 nm or less, and may be 130 nm or more and 180 nm or less. Having a crystallite size within a predetermined range results in an electrode active material with small volumetric changes during charging and discharging. The crystallite size can be determined by performing Rietveld analysis on the XRD measurement results, and then using the analysis results, the RIR (Reference Intensity Ratio) method, and the Scherrer equation.
[0035] The electrode active material of the present disclosure preferably has a silicon clathrate II crystalline phase as the main phase. The term "main phase" refers to a peak belonging to the crystalline phase having the highest diffraction intensity among the peaks observed in X-ray diffraction measurement. The proportion of the silicon clathrate II crystalline phase contained in the electrode active material is, for example, 80% by weight or more, or may be 85% by weight or more, 90% by weight or more, or even 95% by weight or more. The proportion of the silicon clathrate II crystalline phase contained in the electrode active material may be 100% by weight or less. The proportion of the crystalline phase can be determined by performing Rietveld analysis on the XRD measurement results and using the analysis results and the RIR (Reference Intensity Ratio) method.
[0036] The silicon clathrate type II crystalline phase usually belongs to the space group (Fd-3m). In X-ray diffraction measurement using CuKα radiation, the silicon clathrate type II crystalline phase exhibits typical peaks at 2θ = 20.09°, 21.00°, 26.51°, 31.72°, 36.26°, and 53.01°. These peak positions may vary within a range of ±0.50°, ±0.30°, or ±0.10°, respectively.
[0037] In the silicon clathrate II crystal phase, the peak at 2θ=20.09°±0.50° is defined as Peak A, and the peak at 2θ=31.72°±0.50° is defined as Peak B. The intensity of Peak A is defined as I A and the intensity of peak B is I B On the other hand, the maximum intensity at 2θ=22°~23° is I M The range of 2θ=22° to 23° is a range in which peaks of crystalline phases related to Si do not usually appear, and therefore can be used as a reference.
[0038] I A / I M The value of I is preferably greater than 1. A / I MWhen the value of is 1 or less, it can be determined that the silicon clathrate type II crystal phase is not substantially formed. A / I M The value of I is, for example, 1.75 or more, and may be 1.80 or more. A / I M The value of is, for example, 10 or less, and may be 5 or less.
[0039] I B / I M The value of I is preferably greater than 1. B / I M When the value of is 1 or less, it can be determined that the silicon clathrate type II crystal phase is not substantially formed. B / I M The value of I is, for example, 1.35 or more, and may be 1.40 or more, while I B / I M The value of is, for example, 7 or less, and may be 4 or less.
[0040] The electrode active material of the present disclosure may or may not have a silicon clathrate I crystalline phase. "Not having a crystalline phase" means that no peaks of that crystalline phase are observed in X-ray diffraction measurement. The silicon clathrate I crystalline phase usually belongs to the space group (Pm-3n). In X-ray diffraction measurement using CuKα radiation, the silicon clathrate I crystalline phase exhibits typical peaks at 2θ = 19.44°, 21.32°, 30.33°, 31.60°, 32.82°, 36.29°, 52.39°, and 55.49°. These peak positions may vary within a range of ±0.50°, ±0.30°, or ±0.10°, respectively.
[0041] The electrode active material of the present disclosure may or may not have a diamond-type silicon crystalline phase. The proportion of the diamond-type silicon crystalline phase contained in the electrode active material may be, for example, 0 wt. %, greater than 0 wt. %, or 0.2 wt. % or more. On the other hand, the proportion of the diamond-type silicon crystalline phase contained in the electrode active material may be, for example, 5 wt. % or less, or 3 wt. % or less. In addition, the diamond-type silicon crystalline phase exhibits typical peaks at 2θ=28.44°, 47.31°, 56.10°, 69.17°, and 76.37° in X-ray diffraction measurement using CuKα radiation. These peak positions may vary within a range of ±0.50°, ±0.30°, or ±0.10°, respectively.
[0042] When peak C at 2θ=28.44°±0.50° is observed as a peak of the diamond-type silicon crystalline phase, the intensity of peak C is expressed as I C I A / I C is, for example, greater than 1, may be 1.5 or greater, may be 2 or greater, or may be 3 or greater. B / I C The preferred range of I A / I C The preferred range is the same as that of the above.
[0043] The composition of the electrode active material in the present disclosure is not particularly limited, but may include Na x Si 136 It is preferable that the formula be represented by (0≦x≦24). x may be 0 or greater than 0. On the other hand, x may be 20 or less, 10 or less, or 5 or less. The composition of the electrode active material can be determined by, for example, EDX, XRD, XRF, ICP, or atomic absorption spectrometry. In general, an unavoidable oxide film is formed on the surface of the electrode active material. Therefore, the electrode active material may contain a trace amount of O (oxygen). Furthermore, the electrode active material may contain a trace amount of C (carbon) derived from the manufacturing process.
[0044] The electrode active material in the present disclosure may be in the form of primary particles or secondary particles formed by aggregation of primary particles. 50 The average particle size (D) is not particularly limited, but may be, for example, 0.1 μm or more and 50 μm or less, or 0.5 μm or more and 30 μm or less. 50 ) can be calculated, for example, from measurements using a scanning electron microscope (SEM).
[0045] The electrode active material preferably has voids inside the primary particles. The proportion of voids in the primary particles (porosity) is, for example, 4% or more, and may be 10% or more. The porosity may be, for example, 40% or less, and may be 20% or less. The porosity can be determined, for example, by the following procedure. First, a cross section of an electrode layer containing the electrode active material is obtained by ion milling. The cross section is then observed with a scanning electron microscope (SEM) to obtain a photograph of the particles. From the obtained photograph, the silicon portion and the void portion are clearly distinguished using image analysis software and binarized. The areas of the silicon portion and the void portion are determined, and the porosity (%) is calculated using the following formula. Porosity (%) = 100 × (area of void part) / ((area of silicon part) + (area of void part))
[0046] The electrode active material of the present disclosure preferably has many micropores with a pore diameter of 10 nm or less. Pores with a pore diameter of 10 nm or less can accommodate precipitated Li at a higher filling rate than pores with a pore diameter greater than 10 nm, thereby reducing the increase in confining pressure. The pore volume (cumulative pore volume) X of pores with a pore diameter of 10 nm or less is, for example, 0.015 cc / g or more, or may be 0.0167 cc / g or more, 0.020 cc / g or more, 0.023 cc / g or more, or even more than 0.0337 cc / g. Meanwhile, the pore volume X is, for example, 0.09 cc / g or less. The pore volume X can be determined, for example, by mercury porosimeter measurement, BET measurement, gas adsorption method, 3D-SEM, or 3D-TEM. The same method can be used to measure pore volumes other than the pore volume X.
[0047] The electrode active material of the present disclosure preferably has many micropores with a pore diameter of 50 nm or less. Pores with a pore diameter of 50 nm or less can further suppress collapse of the pores by pressing compared to pores with a pore diameter greater than 50 nm and a pore diameter of 100 nm or less. The pore volume Y of pores with a pore diameter of 50 nm or less is, for example, 0.05 cc / g or more, and may be greater than 0.065 cc / g, 0.072 cc / g or more, 0.083 cc / g or more, or 0.10 cc / g or more. On the other hand, the pore volume Y may be, for example, 0.25 cc / g or less, or 0.22 cc / g or less.
[0048] It is preferable that the ratio (X / Y) of the void volume X to the void volume Y is large. X / Y is, for example, 0.17 or more, or may be 0.19 or more, or may be 0.21 or more. On the other hand, X / Y is, for example, 0.41 or less.
[0049] The electrode active material of the present disclosure preferably has many micropores with a pore diameter of 100 nm or less. Pores with a pore diameter of 100 nm or less can be more suppressed from being crushed by pressing than pores with a pore diameter greater than 100 nm. The pore volume Z of pores with a pore diameter of 100 nm or less is, for example, 0.05 cc / g or more, or may be 0.07 cc / g or more, or 0.10 cc / g or more, or may be 0.12 cc / g or more. On the other hand, the pore volume Z is, for example, 0.40 cc / g or less, or may be 0.39 cc / g or less, or may be 0.35 cc / g or less.
[0050] It is preferable that the ratio (X / Z) of the void volume X to the void volume Z is large. X / Z is, for example, 0.10 or more, or may be 0.14 or more, or even 0.16 or more. On the other hand, X / Z is, for example, 0.34 or less.
[0051] The electrode active material of the present disclosure is typically used in batteries. The electrode active material of the present disclosure may be either a negative electrode active material or a positive electrode active material, with the former being preferred. Examples of methods for producing the electrode active material include the production methods described below in "D. Method for producing electrode active material."
[0052] B. Electrode composite material The electrode mixture in the present disclosure contains the above-described electrode active material and at least one of a conductive material and a binder.
[0053] According to the present disclosure, by using the above-described electrode active material, an electrode mixture that undergoes small volume change upon charging and discharging is obtained.
[0054] The electrode mixture contains an electrode active material and at least one of a conductive material and a binder. The electrode active material is the same as that described above in "A. Electrode Active Material." The electrode active material may be either a negative electrode active material or a positive electrode active material, with the former being preferred. That is, the electrode mixture may be either a negative electrode mixture or a positive electrode mixture, with the former being preferred.
[0055] The proportion of the electrode active material in the electrode mixture is, for example, 20% by weight or more, or may be 30% by weight or more, or may be 40% by weight or more. If the proportion of the electrode active material is too low, sufficient energy density may not be obtained. On the other hand, the proportion of the electrode active material is, for example, 80% by weight or less, or may be 70% by weight or less, or may be 60% by weight or less. If the proportion of the electrode active material is too high, the ionic conductivity and electronic conductivity of the electrode mixture may relatively decrease.
[0056] The electrode mixture contains at least one of a conductive material and a binder. Examples of conductive materials include carbon materials, metal particles, and conductive polymers. Examples of carbon materials include particulate carbon materials such as acetylene black (AB) and ketjen black (KB), and fibrous carbon materials such as carbon fiber, carbon nanotubes (CNT), and carbon nanofibers (CNF). Examples of binders include rubber-based binders and fluoride-based binders.
[0057] The electrode mixture may further contain a solid electrolyte. Examples of the solid electrolyte include inorganic solid electrolytes such as sulfide solid electrolytes, oxide solid electrolytes, nitride solid electrolytes, and halide solid electrolytes, and organic polymer electrolytes such as polymer electrolytes. Examples of the sulfide solid electrolyte include solid electrolytes containing Li, X (where X is at least one of P, As, Sb, Si, Ge, Sn, B, Al, Ga, and In), and S. The sulfide solid electrolyte may further contain at least one of O and a halogen element. Examples of the halogen element include F, Cl, Br, and I. The sulfide solid electrolyte may be glass (amorphous) or glass ceramics. Examples of sulfide solid electrolytes include Li2S-P2S5, LiI-Li2S-P2S5, LiI-LiBr-Li2S-P2S5, Li2S-SiS2, Li2S-GeS2, and Li2S-P2S5-GeS2. The electrode mixture may further contain a dispersion medium.
[0058] C.Battery Fig. 2 is a schematic cross-sectional view illustrating a battery according to the present disclosure. The battery 10 shown in Fig. 2 includes a positive electrode layer 1, a negative electrode layer 2, an electrolyte layer 3 disposed between the positive electrode layer 1 and the negative electrode layer 2, a positive electrode current collector 4 that collects current from the positive electrode layer 1, and a negative electrode current collector 5 that collects current from the negative electrode layer 2. In the present disclosure, the positive electrode layer 1 or the negative electrode layer 2 contains the electrode mixture described above in "B. Electrode mixture."
[0059] According to the present disclosure, by using the above-described electrode mixture, a battery with small volume change due to charging and discharging is obtained. As described above, the electrode mixture may be a negative electrode mixture or a positive electrode mixture, but the former is preferable. Below, details of the battery when the electrode mixture is a negative electrode mixture will be described.
[0060] 1. Negative electrode layer The negative electrode layer in the present disclosure contains the above-described electrode mixture (negative electrode mixture). The electrode mixture is the same as that described above in "B. Electrode mixture," and therefore will not be described here. The negative electrode layer may contain an electrolyte, if necessary. The electrolyte is the same as that described in "3. Electrolyte layer." The thickness of the negative electrode layer is, for example, 0.1 μm or more and 1000 μm or less, or may be 0.1 μm or more and 500 μm or less, or may be 0.1 μm or more and 100 μm or less. The negative electrode layer may be formed, for example, by coating the electrode mixture (negative electrode mixture) on a negative electrode current collector.
[0061] 2. Positive electrode layer The positive electrode layer is a layer containing at least a positive electrode active material, and may also contain at least one of an electrolyte, a conductive material, and a binder, as necessary.
[0062] Examples of the positive electrode active material include oxide active materials, such as LiCoO2, LiMnO2, LiNiO2, LiVO2, and LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, etc., rock salt layered active materials, LiMn2O4, Li4Ti5O 12 , Li(Ni 0.5 Mn 1.5 )O4, and olivine type active materials such as LiFePO4, LiMnPO4, LiNiPO4, and LiCoPO4.
[0063] A coating layer containing a Li-ion conductive oxide may be formed on the surface of the oxide active material. This is because it can suppress the reaction between the oxide active material and the solid electrolyte (especially a sulfide solid electrolyte). An example of the Li-ion conductive oxide is LiNbO3. The thickness of the coating layer is, for example, 1 nm or more and 30 nm or less. Furthermore, Li2S, for example, can also be used as the positive electrode active material.
[0064] The positive electrode active material may be in the form of particles, for example. 50 ) is not particularly limited, but may be, for example, 10 nm or more, or may be 100 nm or more. On the other hand, the average particle diameter (D 50 ) is, for example, 50 μm or less, and may be 20 μm or less.
[0065] The electrolyte used in the positive electrode layer is the same as that described in "3. Electrolyte Layer." The conductive material and binder used in the positive electrode layer are the same as those described in "B. Electrode Composite" above, and therefore will not be described here. The thickness of the positive electrode layer is, for example, 0.1 μm or more and 1000 μm or less, or may be 0.1 μm or more and 500 μm or less, or may be 0.1 μm or more and 100 μm or less.
[0066] 3. Electrolyte layer The electrolyte layer is a layer formed between the positive electrode layer and the negative electrode layer, and contains at least an electrolyte. The electrolyte may be a solid electrolyte or a liquid electrolyte (electrolytic solution).
[0067] The solid electrolyte is similar to that described above in "B. Electrode Composite," and therefore will not be described here. The electrolyte preferably contains a supporting salt and a solvent. Examples of supporting salts (lithium salts) for the lithium-ion conductive electrolyte include inorganic lithium salts such as LiPF6, LiBF4, LiClO4, and LiAsF6, and organic lithium salts such as LiCF3SO3, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiN(FSO2)2, and LiC(CF3SO2)3. Examples of solvents used in the electrolyte include cyclic esters (cyclic carbonates) such as ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate (BC), and chain esters (chain carbonates) such as dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC). The electrolyte preferably contains two or more solvents.
[0068] The thickness of the electrolyte layer is, for example, 0.1 μm or more and 1000 μm or less, or may be 0.1 μm or more and 500 μm or less, or may be 0.1 μm or more and 100 μm or less.
[0069] 4. Other configurations The battery according to the present disclosure preferably includes a positive electrode current collector that collects current from the positive electrode layer and a negative electrode current collector that collects current from the negative electrode layer. Examples of materials for the positive electrode current collector include stainless steel, aluminum, nickel, iron, titanium, and carbon. On the other hand, examples of materials for the negative electrode current collector include stainless steel, copper, nickel, and carbon.
[0070] The battery of the present disclosure may further include a restraining jig that applies a restraining pressure to the positive electrode layer, the electrolyte layer, and the negative electrode layer in the thickness direction. In particular, when the electrolyte layer is a solid electrolyte layer, it is preferable to apply a restraining pressure to form good ion conduction paths and electron conduction paths. The restraining pressure is, for example, 0.1 MPa or more, or may be 1 MPa or more, or may be 5 MPa or more. Meanwhile, the restraining pressure is, for example, 100 MPa or less, or may be 50 MPa or less, or may be 20 MPa or less.
[0071] 5.Battery The type of battery in the present disclosure is not particularly limited, but is typically a lithium-ion battery. The battery in the present disclosure may be a liquid battery containing an electrolytic solution as an electrolyte layer, or an all-solid-state battery having a solid electrolyte layer as an electrolyte layer. The battery in the present disclosure may be a primary battery or a secondary battery, but a secondary battery is preferred because it can be repeatedly charged and discharged and is useful, for example, as an on-board battery.
[0072] Examples of uses of the battery include power sources for vehicles such as hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), electric vehicles (BEVs), gasoline-powered vehicles, and diesel-powered vehicles. In particular, it is preferable to use the battery as a driving power source for hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), or electric vehicles (BEVs). The battery may also be used as a power source for mobile objects other than vehicles (for example, trains, ships, and aircraft), and may also be used as a power source for electrical appliances such as information processing devices.
[0073] D. Manufacturing method of electrode active material Fig. 3 is a flowchart illustrating a method for producing an electrode active material according to the present disclosure. In the production method shown in Fig. 3, a Na-Si alloy is first obtained by reacting a Na source and a Si source (alloying step). The Na-Si alloy is then fired to reduce the amount of Na in the Na-Si alloy and produce a silicon clathrate II crystalline phase (firing step). The firing step includes at least a first firing step in which the Na-Si alloy is fired at a temperature below 340°C, and a second firing step in which the compound subjected to the first firing step is fired at a temperature of 340°C or higher. In the firing step, the firing conditions are preferably adjusted so that the crystallite size of the silicon clathrate II crystalline phase is 125 nm or more and 215 nm or less.
[0074] According to the present disclosure, by performing the first and second firing treatments in the firing step, it is possible to obtain an electrode active material that undergoes little volume change due to charge and discharge.
[0075] 1.Alloying process The alloying step in the present disclosure is a step of reacting a Na source and a Si source to obtain a Na—Si alloy.
[0076] The Si source is a particle containing at least Si. The Si source may be simple Si or an alloy of Si and another metal. When the Si source is an alloy, the alloy preferably contains Si as a main component. The proportion of Si in the alloy is, for example, 50 at% or more, or may be 70 at% or more, or may be 90 at% or more.
[0077] The Si source is preferably porous Si having many voids inside the primary particles. Examples of methods for producing the Si source (porous Si) include producing an alloy of Li and Si (Li-Si alloy) and then removing Li from the Li-Si alloy. The Li-Si alloy can be obtained, for example, by mixing Li and Si. The ratio of Li to Si (Li / Si) is, for example, 1.0 or more, or may be 2.0 or more, 3.0 or more, or even 4.0 or more. On the other hand, the Li / Si ratio is, for example, 8.0 or less. Examples of methods for removing Li from the Li-Si alloy include reacting the Li-Si alloy with a Li extractant. Examples of Li extractants include alcohols such as methanol, ethanol, 1-propanol, 1-butanol, 1-pentanol, and 1-hexanol; and acids such as acetic acid, formic acid, propionic acid, and oxalic acid.
[0078] Furthermore, examples of methods for producing a Si source (porous Si) include producing an alloy of Mg and Si (Mg—Si alloy) and then removing Mg from the Mg—Si alloy. The Mg—Si alloy can be obtained, for example, by heating a mixture of Mg and Si. The ratio of Mg to Si (Mg / Si) is, for example, 1.0 or more, or may be 1.5 or more, or even 2.0 or more. On the other hand, the Mg / Si ratio is, for example, 6.0 or less. Examples of methods for removing Mg from an Mg—Si alloy include heating the Mg—Si alloy in an oxygen-containing inert gas atmosphere to convert the Mg in the Mg—Si alloy to MgO, and then removing the MgO with an acid solution. Examples of acid solutions include aqueous solutions containing hydrochloric acid (HCl) and hydrogen fluoride (HF).
[0079] In addition, examples of methods for producing a Si source (porous Si) include a method of producing an alloy of Mg and Si (Mg-Si alloy), then removing Mg from the Mg-Si alloy, then producing an alloy of Si and Li from which the Mg has been removed (Li-Si alloy), and then removing Li from the Li-Si alloy.
[0080] On the other hand, the Na source contains at least Na. Examples of the Na source include metallic Na, NaH, and a metallic Na dispersion in which metallic Na particles are dispersed in oil.
[0081] An example of a method for obtaining a Na-Si alloy by reacting a Na source and a Si source is a method of heating a mixture containing a Na source and a Si source. The heating temperature is, for example, 300°C or higher, and may be 310°C or higher, 320°C or higher, or 340°C or higher. On the other hand, the heating temperature is, for example, 800°C or lower, 600°C or lower, or 450°C or lower. The alloying step is preferably performed in an inert atmosphere such as an Ar atmosphere.
[0082] The Na-Si alloy preferably has a Zintl phase. In X-ray diffraction measurement using CuKα radiation, the Zintl phase exhibits typical peaks at 2θ=16.10°, 16.56°, 17.64°, 20.16°, 27.96°, 33.60°, 35.68°, 40.22°, and 41.14°. These peak positions may vary within a range of ±0.50° or ±0.30°, respectively. The Na-Si alloy preferably has the Zintl phase as its main phase.
[0083] The composition of the Na-Si alloy is not particularly limited, but Na z Si 136 Preferably, the composition is represented by the formula (121≦z≦151). z may be 126 or more, or 131 or more. On the other hand, z may be 141 or less. The Na-Si alloy may contain elements other than Na and Si. Examples of such elements include Li, K, Rb, Cs, Ba, Ga, and Ge.
[0084] 2. Firing process The firing step in the present disclosure is a step of firing the Na—Si alloy to reduce the amount of Na in the Na—Si alloy and generate a silicon clathrate type II crystalline phase.
[0085] The crystallite size of the silicon clathrate II crystalline phase can be controlled by adjusting the firing conditions. Specifically, the crystallite size can be adjusted by considering the balance between nucleation and nucleus growth during firing. The balance between nucleation and nucleus growth during firing can be controlled, for example, by the firing temperature. Here, in order to form a silicon clathrate II crystalline phase from the zintl phase contained in the Na-Si alloy, firing at a relatively high temperature is required. Specifically, the Na-Si alloy needs to be fired at a temperature of 340°C or higher. On the other hand, when firing is performed at a temperature of 340°C or higher, nucleation growth of the silicon clathrate II crystalline phase takes precedence over nucleation of the silicon clathrate II crystalline phase, so the crystallite size of the silicon clathrate II crystalline phase tends to become large.
[0086] In contrast, by firing at a temperature below 340°C before firing at a temperature above 340°C, nucleation takes precedence over nucleus growth, thereby reducing the crystallite size. That is, the firing process usually includes at least a first firing process in which the Na-Si alloy is fired at a temperature below 340°C, and a second firing process in which the compound that has undergone the first firing process is fired at a temperature above 340°C. In addition, in the firing process, it is preferable to adjust the firing conditions so that the crystallite size of the silicon clathrate type II crystalline phase is 125 nm or more and 215 nm or less.
[0087] The first firing treatment is a treatment in which the Na—Si alloy is fired at a temperature below 340°C. In the first firing treatment, a scavenger, which will be described later, may or may not be used. The firing temperature in the first firing treatment is typically below 340°C, may be below 310°C, or may be 300°C or lower. On the other hand, the firing temperature in the first firing treatment is, for example, 250°C or higher, may be 270°C or higher, or may be 280°C or higher. The firing time in the first firing treatment is, for example, 1 hour or longer and 50 hours or shorter, or may be 5 hours or longer and 30 hours or shorter.
[0088] The second firing treatment is a treatment in which the compound that has been subjected to the first firing treatment is fired at a temperature of 340°C or higher. In the second firing treatment, it is preferable to use a scavenger, which will be described later, and in particular, it is preferable to use AlF3. The firing temperature in the second firing treatment is usually 340°C or higher, and may be 360°C or higher. On the other hand, the firing temperature in the second firing treatment may be, for example, 450°C or lower. The firing time in the second firing treatment is, for example, 1 hour or more and 120 hours or less, or may be 10 hours or more and 80 hours or less. The compound that has been subjected to the second firing treatment preferably has a silicon clathrate type II crystalline phase.
[0089] The calcination step may include a third calcination treatment in which the compound that has undergone the second calcination treatment is calcined at a temperature of 340°C or higher. In the third calcination treatment, it is preferable to use a scavenger, as described below, and in particular, it is preferable to use ZnCl2. The calcination temperature in the third calcination treatment is usually 340°C or higher, and may be 360°C or higher. On the other hand, the calcination temperature in the third calcination treatment may be, for example, 450°C or lower. The calcination time in the third calcination treatment is, for example, 1 hour or more and 120 hours or less, or may be 10 hours or more and 80 hours or less. It is preferable that the compound that has undergone the third calcination treatment has a silicon clathrate type II crystalline phase as a main phase.
[0090] In the firing step, it is preferable to use a scavenger that captures Na in the Na-Si alloy. One example of the scavenger is a Na getter agent that reacts with Na vapor generated from the Na-Si alloy. The Na getter agent is disposed, for example, without contacting the Na-Si alloy. Examples of the Na getter agent include SiO, MoO3, FeO, and Fe3O4. When a Na getter agent is used, it is preferable to perform the firing step in a reduced pressure atmosphere.
[0091] Another example of a scavenger is a Na-trapping agent that directly reacts with the Na-Si alloy to receive Na. The Na-trapping agent is placed in contact with the Na-Si alloy. Examples of the Na-trapping agent include CaCl2, AlF3, CaBr2, CaI2, Fe3O4, FeO, MgCl2, ZnO, ZnCl2, and MnCl2. When using a Na-trapping agent, the firing process may be performed in a reduced pressure atmosphere or in an atmospheric pressure atmosphere.
[0092] In addition, the balance between nucleation and nucleus growth during firing can be controlled, for example, by the type, particle size, and amount of the scavenger. For example, by reducing the particle size of the Na trapping agent, which is the scavenger, the contact area between the Na trapping agent and the Na-Si alloy increases. This makes it easier for Na to be extracted from the Na-Si alloy, and nucleation takes precedence over nucleus growth, allowing the crystallite size to be adjusted to be small. On the other hand, it is presumed that if the contact area between the Na trapping agent and the Na-Si alloy increases too much, a diamond-type silicon crystalline phase, which is more stable than the silicon clathrate II crystalline phase, is more likely to be generated.
[0093] 3. Electrode active material The electrode active material obtained by each of the above-mentioned steps has a silicon clathrate II crystalline phase. Furthermore, it is preferable that the crystallite size of the silicon clathrate II crystalline phase is within a predetermined range. The preferred embodiments of the electrode active material are the same as those described above in "A. Electrode active material."
[0094] E. Manufacturing method of electrode mixture The present disclosure provides a method for producing an electrode composite, the method comprising: a preparation step of preparing an electrode active material by the above-described method for producing an electrode active material; and a mixing step of mixing the electrode active material with at least one of a conductive material and a binder to obtain an electrode composite.
[0095] According to the present disclosure, by using the above-described electrode active material, an electrode mixture with small volume change due to charging and discharging can be obtained. The preparation process is the same as that described above in "D. Method for producing electrode active material."
[0096] The electrode mixture typically contains an electrode active material and at least one of a conductive material and a binder. The conductive material and binder are the same as those described above in "B. Electrode mixture." The electrode mixture may or may not further contain a dispersion medium. The electrode mixture is typically obtained by mixing the electrode active material with at least one of a conductive material and a binder. There are no particular limitations on the mixing method, and known methods can be used. Preferred aspects of the resulting electrode mixture are the same as those described above in "B. Electrode mixture."
[0097] F. Battery manufacturing method The present disclosure provides a method for manufacturing a battery, including: a preparation step of preparing an electrode active material by the above-described method for manufacturing an electrode active material; a mixing step of mixing the electrode active material with at least one of a conductive material and a binder to obtain an electrode mixture; and an electrode layer formation step of forming an electrode layer using the electrode mixture.
[0098] According to the present disclosure, by using the above-described electrode active material, a battery with small volume change due to charging and discharging can be obtained. The preparation process and mixing process are the same as those described above in "D. Method for producing electrode active material" and "E. Method for producing electrode mixture."
[0099] The electrode layer forming step is a step of forming an electrode layer using the electrode mixture. The method for forming the electrode layer is not particularly limited, and known methods can be used. Examples of methods for forming the electrode layer include a method in which the electrode mixture is applied to an electrode current collector. When forming the electrode layer, a pressing process may be performed to press the electrode layer in the thickness direction. Examples of pressing processes include roller pressing and flat plate pressing. Furthermore, when the electrode mixture is a slurry containing a dispersion medium, it is preferable to dry the electrode mixture after applying it to the electrode current collector.
[0100] The electrode layer forming step may be a positive electrode layer forming step of forming a positive electrode layer, or may be an anode layer forming step of forming an anode layer. The method for forming the battery is not particularly limited, and known methods can be used. Preferred aspects of the resulting battery are the same as those described above in "C. Battery."
[0101] The present disclosure is not limited to the above-described embodiments. The above-described embodiments are merely examples, and any configuration that is substantially identical to the technical idea described in the claims of the present disclosure and that provides similar effects is included within the technical scope of the present disclosure. [Example]
[0102] [Example 1] In an Ar atmosphere, metallic Li and Si powder (manufactured by Kojundo Kagaku Co., Ltd., SIEPB32) were weighed out in a molar ratio of 4:1 and mixed in a mortar for 1 hour. 15 A Li-Si alloy with a Si4 phase was obtained. The resulting Li-Si alloy was reacted with ethanol under an Ar atmosphere. Acetic acid was then added, and the liquid and solid components were separated by filtration. The separated solid component was vacuum dried at 120°C to obtain powdered porous Si.
[0103] The resulting porous Si and NaH (Na source) were weighed to a molar ratio of NaH / porous Si = 1.1 / 1 and mixed using a cutter mill. The resulting mixture was placed in a reaction vessel and fired at 475°C for 10 hours in an Ar atmosphere to obtain a Na-Si alloy.
[0104] The resulting Na-Si alloy was mixed with AlF3, a sodium trapping agent. The AlF3 was classified using a 35 μm mesh sieve and a 75 μm mesh sieve. The resulting mixture was subjected to a first firing treatment under conditions of an Ar atmosphere at 290°C for 10 hours, followed by a second firing treatment under conditions of an Ar atmosphere at 340°C for 40 hours. The resulting compound was then placed in a 6 wt% HNO3 aqueous solution and stirred for 1 hour. The stirred compound was then filtered, and the solid content was dried at 120°C for 12 hours to obtain a powder.
[0105] The obtained powder and zinc chloride (ZnCl2) were weighed to a molar ratio of powder:ZnCl2 = 6:1 and mixed using a cutter mill. The obtained mixture was subjected to a third firing treatment under conditions of an Ar atmosphere, 345°C, and 15 hours. The obtained compound was then placed in a 6 wt% HNO3 aqueous solution and stirred for 1 hour. The stirred compound was then filtered, and the solid content was dried under conditions of 120°C and 12 hours to obtain a powder.
[0106] The obtained powder was added to a 3 wt% aqueous solution of hydrogen fluoride (HF) and stirred for 3 hours. The stirred compound was then suction filtered, and the solid content was dried at 120°C for 12 hours to obtain a powder. After drying, the obtained powder was added to acetone, and coarse particles were removed using a resin sieve to obtain an electrode active material.
[0107] [Example 2] An electrode active material was obtained in the same manner as in Example 1, except that the second baking treatment was carried out under conditions of an Ar atmosphere, 340° C., and 80 hours.
[0108] [Example 3] An electrode active material was obtained in the same manner as in Example 1, except that the second baking treatment was carried out under conditions of an Ar atmosphere, 340° C., and 60 hours.
[0109] [Example 4] An electrode active material was obtained in the same manner as in Example 1, except that the first firing treatment was carried out under conditions of an Ar atmosphere, 280°C, and 10 hours, and the second firing treatment was carried out under conditions of an Ar atmosphere, 340°C, and 20 hours.
[0110] [Example 5] An electrode active material was obtained in the same manner as in Example 1, except that the first firing treatment was carried out under conditions of an Ar atmosphere, 280°C, and 10 hours, and the second firing treatment was carried out under conditions of an Ar atmosphere, 340°C, and 100 hours.
[0111] [Comparative Example 1] An electrode active material was obtained in the same manner as in Example 1, except that the first firing treatment was carried out under conditions of an Ar atmosphere, 340°C, and 10 hours, and the second firing treatment was carried out under conditions of an Ar atmosphere, 340°C, and 120 hours.
[0112] Comparative Example 2 AlF was placed in a container together with crushing balls (φ1 μm) and pulverized using a planetary ball mill (Fritsch) at 200 rpm for 3 hours. An electrode active material was obtained in the same manner as in Example 1, except that the pulverized AlF was used in a first firing treatment under conditions of an Ar atmosphere at 310°C for 10 hours and a second firing treatment under conditions of an Ar atmosphere at 340°C for 10 hours.
[0113] [evaluation] (XRD measurement) X-ray diffraction (XRD) measurements using CuKα radiation were performed on the electrode active materials obtained in Examples 1 to 5 and Comparative Examples 1 and 2. As a result, it was confirmed that all of the electrode active materials had a silicon clathrate type II crystalline phase as the main phase.
[0114] The intensity of peak A located near 2θ=20.09° in the silicon clathrate II crystal phase is I AThe intensity of peak B located near 2θ = 31.72° is I B The maximum intensity at 2θ = 22° to 23° was defined as I M And I A / I M and I B / I M As a result, the electrode active materials obtained in Examples 1 to 5 and Comparative Examples 1 and 2 all had I A / I M is greater than 1 and I B / I M was also greater than 1.
[0115] Rietveld analysis was performed using XRD analysis software (PDXL manufactured by RIGAKU Corporation), and the crystallite size of the silicon clathrate II crystalline phase was determined using the analysis results, the RIR (Reference Intensity Ratio) method, and the Scherrer equation. The results are shown in Table 1. Furthermore, all of the electrode active materials obtained in Examples 1 to 5 and Comparative Examples 1 and 2 contained a small amount of diamond-type silicon crystalline phase. The proportion of the diamond-type silicon crystalline phase (crystalline Si content) was determined using the Rietveld analysis results and the RIR method. The results are shown in Table 1.
[0116] (SEM observation) The average particle size (D 50 ) was determined by observation using a scanning electron microscope (SEM). The results are shown in Table 1. As shown in Table 1, the average particle diameter D 50 In this way, the average particle size (D 50 ) is preferably 0.5 μm or more and 5 μm or less.
[0117] (Measurement of volume expansion rate) All-solid-state batteries were fabricated using the electrode active materials obtained in Examples 1 to 5 and Comparative Examples 1 and 2 as negative electrode active materials, respectively, by the following fabrication method.
[0118] (1) Preparation of the negative electrode The resulting electrode active material, sulfide solid electrolyte (Li2S-P2S5-based glass ceramic), conductive material (VGCF), and butyl butyrate solution containing 5 wt% PVDF-based binder, and butyl butyrate were added to a polypropylene container and stirred for 30 seconds using an ultrasonic disperser (UH-50, manufactured by SMT). The container was then shaken for 30 minutes using a shaker (TTM-1, manufactured by Shibata Scientific Co., Ltd.). The mixture was applied to a negative electrode current collector (Cu foil, manufactured by UACJ) using an applicator by the blade method and dried on a hot plate at 100 °C for 30 minutes. This resulted in a negative electrode comprising a negative electrode current collector and a negative electrode layer.
[0119] (2) Preparation of the positive electrode The positive electrode active material (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 A butyl butyrate solution containing 5 wt% PVDF binder (O2, average particle size 6 μm), a sulfide solid electrolyte (Li2S-P2S5-based glass ceramic), a conductive material (VGCF), and butyl butyrate were added and stirred for 30 seconds using an ultrasonic disperser (UH-50, manufactured by SMT). The container was then shaken for 3 minutes using a shaker (TTM-1, manufactured by Shibata Scientific Co., Ltd.), followed by another 30 seconds of stirring using the ultrasonic disperser and another 3 minutes of shaking using the shaker. The mixture was applied to a positive electrode current collector (Al foil, manufactured by Showa Denko KK) using an applicator by the blade method and dried for 30 minutes on a hot plate at 100 °C. This resulted in a positive electrode comprising a positive electrode current collector and a positive electrode layer. The area of the positive electrode was smaller than that of the negative electrode.
[0120] (3) Preparation of solid electrolyte layer A sulfide solid electrolyte (Li2S-P2S5-based glass ceramic), a heptane solution containing 5 wt% butylene rubber binder, and heptane were added to a polypropylene container and stirred for 30 seconds using an ultrasonic disperser (UH-50, manufactured by SMT). The container was then shaken for 30 minutes using a shaker (TTM-1, manufactured by Shibata Scientific Co., Ltd.). The mixture was applied to a release sheet (Al foil) using an applicator by the blade method and dried on a hot plate at 100°C for 30 minutes. This resulted in a transfer member having a release sheet and a solid electrolyte layer.
[0121] (4) Fabrication of all-solid-state batteries A solid electrolyte layer for bonding was placed on the positive electrode layer of the positive electrode, and the resulting mixture was set in a roll press and pressed at 100 kN / cm and 165° C. This produced a first laminate.
[0122] Next, the negative electrode was set in a roll press and pressed at 60 kN / cm and 25°C. This resulted in a pressed negative electrode. Thereafter, a solid electrolyte layer for bonding and a transfer member were arranged in this order from the negative electrode layer side. At this time, the solid electrolyte layer for bonding and the solid electrolyte layer on the transfer member were arranged so as to face each other. The obtained laminate was set in a planar uniaxial press and temporarily pressed at 100 MPa and 25°C for 10 seconds. Then, the release sheet was peeled off from the solid electrolyte layer. This resulted in a second laminate.
[0123] Next, the bonding solid electrolyte layer of the first laminate and the solid electrolyte layer of the second laminate were arranged to face each other, and then set in a flat uniaxial press and pressed at 200 MPa and 120°C for 1 minute, thereby obtaining an all-solid-state battery.
[0124] (5) Measurement of volume expansion rate The obtained all-solid-state battery was charged, and the volume expansion rate was measured. The test conditions were a confining pressure (constant size) of 5 MPa, a charge of 0.1 C, and a cutoff voltage of 4.55 V. The confining pressure at 4.55 V was measured, and the increase in confining pressure from the state before charging was determined, thereby calculating the volume expansion rate. The results are shown in Table 1 and FIG. 4. The volume expansion rate results in Table 1 and FIG. 4 are relative values, with the result of Comparative Example 1 set to 100.
[0125] [Table 1]
[0126] As shown in Table 1, Example 3 and Comparative Example 1 had similar amounts of crystalline Si, but there was a large difference in the volume expansion coefficient. Furthermore, as shown in Table 1 and FIG. 4, it was confirmed that Examples 1 to 5 had smaller volume expansion coefficients than Comparative Examples 1 and 2. Thus, by keeping the crystallite size within a predetermined range, it was possible to reduce the volume expansion coefficient. Among Examples 1 to 5, Example 4 (crystallite size: 133 nm), Example 1 (crystallite size: 157 nm), and Example 3 (crystallite size: 176 nm) had particularly small volume expansion coefficients. In other words, it was confirmed that a crystallite size of 130 nm or more and 180 nm or less is particularly preferable. [Explanation of symbols]
[0127] 1...Positive electrode layer 2...Anode layer 3...electrolyte layer 4...Positive electrode current collector 5...Negative electrode current collector 10...battery
Claims
1. An electrode active material having a silicon clathrate II type crystalline phase, The electrode active material, wherein the crystallite size of the crystalline phase is 125 nm or more and 215 nm or less.
2. 2. The electrode active material according to claim 1, wherein the crystallite size of the crystalline phase is 130 nm or more and 180 nm or less.
3. 2. The electrode active material according to claim 1, wherein the proportion of the diamond-type silicon crystal phase contained in the electrode active material is 0% by weight or more and 3% by weight or less.
4. 2. The electrode active material according to claim 1, wherein the proportion of the diamond-type silicon crystal phase contained in the electrode active material is 0.2% by weight or more and 3% by weight or less.
5. The electrode active material according to claim 1 , which has the silicon clathrate II type crystal phase as a main phase.
6. The electrode active material according to claim 1 , wherein the electrode active material has voids inside primary particles.
7. The electrode active material according to claim 6 , wherein the ratio of voids is 4% or more and 40% or less.
8. An electrode mixture comprising the electrode active material according to any one of claims 1 to 7 and at least one of a conductive material and a binder.
9. The electrode mixture of claim 8 , further comprising a solid electrolyte.
10. The electrode mixture according to claim 9 , wherein the solid electrolyte contained in the electrode mixture is a sulfide solid electrolyte.
11. A battery having a positive electrode layer, a negative electrode layer, and an electrolyte layer disposed between the positive electrode layer and the negative electrode layer, A battery, wherein the positive electrode layer or the negative electrode layer contains the electrode mixture according to claim 8 .
12. The battery of claim 11 , wherein the negative electrode layer contains the electrode mix.
13. 12. The battery of claim 11, wherein the electrolyte layer comprises a solid electrolyte.
14. the solid electrolyte included in the electrolyte layer is a sulfide solid electrolyte, 14. The battery of claim 13, wherein the electrolyte layer has a thickness of 0.1 μm or more and 100 μm or less.
15. 15. The battery of claim 14, wherein the positive electrode layer comprises a rock salt layered active material.
16. an alloying step of reacting a Na source and a Si source to obtain a Na-Si alloy; a firing step of firing the Na-Si alloy to reduce the amount of Na in the Na-Si alloy and generate a silicon clathrate II crystal phase; having The firing step includes: A first firing treatment in which the Na-Si alloy is fired at a temperature of less than 340°C; A second firing process in which the compound subjected to the first firing process is fired at a temperature of 340° C. or higher; The method for producing an electrode active material has at least the above-mentioned features.
17. The method for producing an electrode active material according to claim 16, wherein in the firing step, firing conditions are adjusted so that the crystallite size of the crystalline phase is 125 nm or more and 215 nm or less.
18. A preparation step of preparing an electrode active material by the method for producing an electrode active material according to claim 16 or 17; a mixing step of mixing the electrode active material with at least one of a conductive material and a binder to obtain an electrode mixture; The method for producing an electrode mixture comprising the steps of:
19. A preparation step of preparing an electrode active material by the method for producing an electrode active material according to claim 16 or 17; a mixing step of mixing the electrode active material with at least one of a conductive material and a binder to obtain an electrode mixture; an electrode layer forming step of forming an electrode layer using the electrode mixture; A method for manufacturing a battery comprising the steps of:
Citation Information
Patent Citations
Electrode active material, electrode, battery, manufacturing method of electrode active material
JP2016066418A
Active material and battery
JP2020017513A
Negative electrode active material including silicon clathrate ii
JP2021034279A
Production method of silicon-based active material
JP2021152990A
Active material, negative electrode layer, battery and these manufacturing methods
JP2021158003A